Survival and predictors of death in tuberculosis/HIV coinfection cases in Porto Alegre, Brazil: A historical cohort from 2009 to 2013. - Évelin Maria Brand; Maíra Rossetto; Bruna Hentges; Gerson Barreto Winkler; Erica Rosalba Mallmann Duarte; Lucas Cardoso da Silva; Andrea Fachel Leal; Daniela Riva Knauth; Danielle Lodi Silva; George Henrique Aliatti Mantese; Tiane Farias Volpato; Paulo Ricardo Bobek; et al. (Public Library of Science (PLoS), 2021)
Background Tuberculosis is a curable disease, which remains the leading cause of death among infectious diseases worldwide, and it is the leading cause of death in people living with HIV. The purpose is to examine survival and predictors of death in Tuberculosis/HIV coinfection cases from 2009 to 2013. Methods We estimated the survival of 2,417 TB/HIV coinfection cases in Porto Alegre, from diagnosis up to 85 months of follow-up. We estimated hazard ratios and survival curves. Results The adjusted risk ratio (aRR) for death, by age, hospitalization, and Directly Observed Treatment was 4.58 for new cases (95% CI: 1.14-18.4), 4.51 for recurrence (95% CI: 1.11-18.4) and 4.53 for return after abandonment (95% CI: 1.12-18.4). The average survival time was 72.56 ± 1.57 months for those who underwent Directly Observed Treatment and 62.61 ± 0.77 for those who did not. Conclusions Case classification, age, and hospitalization are predictors of death. The occurrence of Directly Observed Treatment was a protective factor that increased the probability of survival. Policies aimed at reducing the mortality of patients with TB/HIV coinfection are needed.